Digital Native Advertising: Practitioner Perspectives and a Research Agenda. Issue 2 (3rd July 2017) - Harms, Bianca; Bijmolt, Tammo H.A.; Hoekstra, Janny C.
ABSTRACT: Digital native advertising is a subtle form of digital advertising that is integrated closely with its context. Practitioners are increasingly assigning budgets to this advertising strategy. On the basis of 22 in-depth expert interviews with senior executives of advertising brands, publishing companies, and media agencies, this study provides new insights into the effectiveness of digital native advertising. We also shed light on factors in the field of content and context of digital native advertising that influence its performance. We present 10 key propositions that reflect practitioners' perspectives and form an agenda for further scientific research in the field of digital native advertising.